Estimating mode choice inertia and price elasticities after a price intervention: Evidence from three months of almost fare-free public transport in Germany - Maria Fernanda Guajardo Ortega; Heike Link (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
This study analyses the behavioural response of travellers on a temporal reduction of public transport prices in Germany through the so-called 9 Euro Ticket during summer 2022. The focus is on the inertia effect, e.g. the resistance to change behaviour, on people's travel mode decisions for commuter trips. We estimate mixed logit models for nearly 7,000 commuter trips, based on GPS-tracking data collected as a panel dataset before and after the price intervention. We find significant inertia effects for all travel modes except walking, with negative effects for car and positive effects for public transport and cycling, indicating that car users are less willing to change travel mode while cyclists and public transport users tend to be less resistant. Cross-elasticities of car with respect to public transport attributes are higher than the cross-elasticities of public transport with respect to car attributes such as in-vehicle time and cost. This effect is even higher in the inertia model. Our modelling results suggest that car travel is inelastic and characterised by negative inertia, with a relationship between both effects. Future policy interventions such as the 49-Euro ticket should therefore not focus on price reductions alone, but need additionally to improve other attributes of public transport such as frequency, reliability, safety and comfort in order to incentivise motorists to shift from car to public transport.
Keywords: C23; C25; R41; 330; Inertia; Price elasticities; Revealed preference; GPS panel data; Mode choice